PLEASE CHECK

Thank you for the opportunity to help you with your question!

f(x)=5x-2

g(x) =4-x^2

(f g) (x) =f[g(x)]

=f[4-x^2]

=5(4-x^2)-2

=20-5x^2-2

=18-5x^2

(g f) (x) =g[f(x)

=g[5x-2]

=4-[5x-2]^2

=4-[25x^2-20x+4]

=20x-25x^2

thsi is answer is an exact number

u have not specified value of x

what is x=?

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up